Semiconductor Switching Devices. .Future Trends - Ahmad, S. (Defence Science Journal, 2013)
A variety of semiconductor devices and circuits have been successfully developed usingconduction properties of electrons and holes in a number of elemental and compound semiconductors.Carriers confinement in a potential well, formed out of a thin layer of lower band gap materialsandwitched between two layers of a higher band gap material, has been extended from one to two andthree dimensions. Resultant of two-dimensional carrier sheet, quantum wire and quantum dot havingdiscrete energy levels arising out of quantisation are being presently explored for possible device applications. A number of devices have been fabricated using resonant tunneling across a thin potentialbarrier. This has opened up several newer possibilities of using such structures for various electronicand optoelectronic devices and circuits applications as tunneling is relatively faster than conductionprocess. While looking into the interband tunneling between two quantum dots, possibility of a singleelectron switching has also been examined carefully. The idea of a single electron switching isconceptually being extended from quantl,lm dots to molecules and atoms ultimately. Simulations basedon transmission of electrons through a chain of molecules and atoms have shown that tens of THz speed and functional device density 1012 devices/mm2 are possible with such schemes. Devices basedon atom relay transistor (ART) will be ultimate in its performance of switching speed. A brief onpresent-day situation followed by future proposals of fast switching devices for informationelectronics has been discussed.